Prevalidation of the cAMP-PTx reporter assay for quantitative assessment of pertussis toxin activity. Issue 32 (30th July 2022) - de Brouwer, L.; David, D.; Espitia Ballestas, M.; Sloots, A.; Hoonakker, M.E.
Abstract: Testing for inactivation of pertussis toxin and reversion to toxicity in aP vaccines has historically relied on the murine histamine sensitization test, that lacks mechanistic understanding, suffers from standardization problems and is associated with severe animal suffering. Though the regulatory requirements for in vivo testing of acellular pertussis (aP) vaccine products have been waived in Europe, it is still common practice globally. Easy and quantitative in vitro methods are therefore urgently needed. One of the alternatives under development is our reporter cell line - CHO-CRE cells - that carries a cAMP-reporter construct. After exposure to pertussis toxin, cells are stimulated with a low concentration of forskolin to allow detection of pertussis toxin dependent changes in intracellular cAMP levels. Here, the results of two prevalidation studies with purified pertussis toxin and pertussis toxin spiked aP vaccines are described that were performed according to the principles of the ICH Q2(R1) guidelines for a content assay. We confirmed the assay's specificity, accuracy, precision, linearity and range. The cAMP-PTx reporter assay allows for objective, reliable and quantitative assessment of pertussis toxin levels in aP vaccines and can thereby boost broad and global replacement of the histamine sensitization test.